EP311/#1038 Secreted HLA-G profiling in epithelial ovarian carcinoma ascites. (4th December 2022) - Babay, Wafa; Boujelbene, Nadia; Zemni, Ines; Dhouioui, Sabrine; Safta, Ines Ben; Rebmann, Vera; Zidi, Ines
Abstract : Objectives: Human leukocyte antigen (HLA)-G expression has been correlated with disease status and cancer patients'outcome. In this study, we aimed to investigate the expression levels of both free soluble molecules (sHLA-G) and via extracellular vesicles as a membrane anchored molecule (HLA-GEV ) in ascites from epithelial ovarian carcinoma (EOC) patients. We also explored their correlation with CA-125 tumor marker levels and histological subtypes. Methods sHLA-G and HLA-GEV levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA) method in 30 ascites from EOC patients. Results: Secreted HLA-G was detected in most of the ascites of EOC patients (sHLA-G 93%; HLA-GEV 70%) with increased levels (sHLA-G: 6.46 ng/ml and HLA-GEV : 3.62ng/ml). Secreted HLA-G levels were highly increased in patients with serous ovarian carcinoma versus other subtypes (sHLA-G : 6.94ng/ml vs 4.62ng/ml, and HLA-GEV : 4.20ng/ml vs 1.45ng/ml, respectively). Interestingly, sHLA-G level was increased in EOC patients with high CA-125 tumor marker levels (CA125 ≥35U/ml: 7.20ng/ml vs CA-125 <35U/ml: 3.51 ng/ml). Similarly, HLA-GEV level was increased in EOC patients with high CA-125 tumor marker levels (CA125 ≥35U/ml: 4.16ng/ml vs CA-125 <35U/ml: 1.89ng/ml). Conclusions: Our preliminary data established that both sHLA-G and HLA-GEV may provide an interesting new opportunity as tumor markers to evaluate patients with suspected ovarian cancer. Further studies still needed to consolidate our finding and clearly establish secreted HLA-G as new biomarkers for monitoring the disease.